2016
DOI: 10.1002/dc.23463
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of immunocytochemistry and fluorescence in situ hybridization on fine‐needle aspiration cytology samples of breast cancers: A comparative study

Abstract: The correlation of ICC and IHC is moderate regarding ER and Her2 expression of the same tumor. FISH performed on FNAB samples is suitable to categorize primary and metastatic breast cancer in regard of HER2 gene amplification status and can be used as a predictive test in respect of therapies targeting HER2. Diagn. Cytopathol. 2016;44:466-471. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(34 reference statements)
0
5
1
Order By: Relevance
“…In our study, formalin-fixed cell block sections were used for breast biomarker testing. Previous studies suggested that IHCs for HER2, ER and PR performed on FFPE cell blocks were reliable in predicting the expression of these markers [18,19,20,21,22]. In our study, however, the overall change rate for ER was significantly higher in the cytological specimens than in the surgical specimens.…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, formalin-fixed cell block sections were used for breast biomarker testing. Previous studies suggested that IHCs for HER2, ER and PR performed on FFPE cell blocks were reliable in predicting the expression of these markers [18,19,20,21,22]. In our study, however, the overall change rate for ER was significantly higher in the cytological specimens than in the surgical specimens.…”
Section: Discussioncontrasting
confidence: 55%
“…-mammary cells-for the diagnosis of breast cancer [4]; -cervical cells-for the diagnosis of concomitant diseases [5] [6];…”
Section: Introductionmentioning
confidence: 99%
“…1 First of all, reliability (precision) and validity (accuracy) are two completely different methodological issues which should not be confused. They aimed to assess the diagnostic accuracy of ancillary tests applied to fine-needle aspiration cytology (FNAB) in breast tumors and metastases, as a favorable first choice.…”
mentioning
confidence: 99%
“…The authors compared ER and Her2 immunocytochemical (ICC) as well as immunohistochemical (IHC) staining and HER2 fluorescence in situ hybridization (FISH). 1 First of all, reliability (precision) and validity (accuracy) are two completely different methodological issues which should not be confused. (Title of the paper and the aim of the authors indicate to this confusion).…”
mentioning
confidence: 99%
See 1 more Smart Citation